School strategies in instilling student discipline to improving education quality - Arga Bagus Pratama Dyah Aan Firman Syah; Nur Janah; Deny Hadi Siswanto (Universitas Pendidikan Indonesia, 2025)
Discipline as a significant factor in improving the quality of education and shaping student character needs to be upheld in the implementation of education. Therefore, this study aims to determine the school's strategy in instilling student discipline values at SMA Muhammadiyah Mlati. This research employs a descriptive qualitative method, utilizing data collection techniques that include observation and interviews with the principal, vice principal for student affairs, and homeroom teachers. The results showed that the implemented strategies included the enforcement of school regulations, habituation of religious activities such as Zuhur prayer in congregation, and parental involvement in supporting student discipline. Supporting factors in the implementation of discipline include the active role of the principal, teachers, and educators. However, the main challenge faced is students' low awareness of time discipline and compliance with school rules. To overcome this obstacle, the school employs educational sanctions and moral coaching on an ongoing basis. It can be concluded that the strategies implemented focus on strengthening character and promoting discipline as part of the school culture, thereby improving the quality of education. Abstrak Kedisiplinan sebagai faktor utama dalam meningkatkan kualitas pendidikan dan membentuk karakter siswa perlu ditegakkan pada pelaksanaan pendidikan. Maka dari itu, penelitian ini bertujuan untuk mengetahui strategi sekolah dalam menanamkan nilai-nilai kedisiplinan siswa di SMA Muhammadiyah Mlati. Penelitian ini menggunakan metode kualitatif deskriptif dengan teknik pengumpulan data melalui observasi dan wawancara dengan kepala sekolah, wakil kepala sekolah bidang kesiswaan, dan wali kelas. Hasil penelitian menunjukkan bahwa strategi yang diterapkan meliputi penerapan peraturan sekolah, pembiasaan kegiatan religius seperti salat Zuhur berjamaah, serta keterlibatan orang tua dalam mendukung kedisiplinan siswa. Faktor pendukung dalam penerapan disiplin meliputi peran aktif kepala sekolah, guru, serta tenaga pendidik. Namun, tantangan utama yang dihadapi adalah rendahnya kesadaran siswa terhadap disiplin waktu dan kepatuhan terhadap aturan sekolah. Dalam mengatasi hambatan ini, pihak sekolah menerapkan sanksi edukatif dan pembinaan moral secara berkelanjutan. Dapat disimpulkan bahwa strategi yang diterapkan berfokus pada penguatan karakter dan pembiasaan disiplin sebagai bagian dari budaya sekolah dalam meningkatkan kualitas pendidikan. Kata Kunci: kedisiplinan siswa; manajemen sekolah; strategi sekolah